2020
DOI: 10.1186/s12884-020-03470-1
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of desire for more children among childbearing women in sub-Saharan Africa: implications for fertility control

Abstract: Background Despite the extensive research on fertility desires among women the world over, there is a relative dearth of literature on the desire for more children in sub-Saharan Africa (SSA). This study, therefore, examined the desire for more children and its predictors among childbearing women in SSA. Methods We pooled data from 32 sub-Saharan African countries’ Demographic and Health Surveys. A total of 232,784 married and cohabiting women with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

26
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 42 publications
26
32
2
Order By: Relevance
“…These authors argue that more educated men have higher average earnings, making it possible to afford a larger family. Contrary to the findings of previous studies [ 38 , 71 , 72 ], the current study found no statistically significant association between the level of education of women and desire for more children. However, we found the highest prevalence of desire for more children among women with secondary/higher education in Niger.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These authors argue that more educated men have higher average earnings, making it possible to afford a larger family. Contrary to the findings of previous studies [ 38 , 71 , 72 ], the current study found no statistically significant association between the level of education of women and desire for more children. However, we found the highest prevalence of desire for more children among women with secondary/higher education in Niger.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, Dyer et al [ 49 ] indicated that some women are divorced because they cannot have children. This finding is similar to previous studies by Ahinkorah et al [ 38 ], Hacettepe University Institute of Population Studies [ 45 ] and Ocalan et al [ 50 ], which showed that the desire for more children declined greatly with the increase in the number of children of a childbearing woman. Other studies that made similar observations include Adebowale et al [ 51 ], Babalola et al [ 52 ], Eklund [ 53 ], and De Silva [ 54 ] in Nigeria, China, and Sri Lanka.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Studies have established that fertility preference is not stable and changes due to prevailing circumstances (Liefbroer, 2009;Trinitapoli & Yeatman, 2018). Furthermore, studies conducted in sub-Saharan Africa (SSA) including Ghana have identified a number of factors as predictors of high fertility preference (Ahinkorah et al, 2020;Kodzi et al, 2010;Odusina et al, 2020;Van Lith et al, 2013). Findings from these studies suggest positive relationship between fertility preference and actual fertility.…”
mentioning
confidence: 99%